2017
DOI: 10.1073/pnas.1708710114
|View full text |Cite
|
Sign up to set email alerts
|

Rat embryonic stem cells produce fertile offspring through tetraploid complementation

Abstract: Pluripotency of embryonic stem cells (ESCs) can be functionally assessed according to the developmental potency. Tetraploid complementation, through which an entire organism is produced from the pluripotent donor cells, is taken as the most stringent test for pluripotency. It remains unclear whether ESCs of other species besides mice can pass this test. Here we show that the rat ESCs derived under 2i (two small molecule inhibitors) conditions at very early passages are able to produce fertile offspring by tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…However, rat PSCs are less robust than mouse PSCs, partly because of the difficulties of handling and clonal selection after genetic manipulation 20 , 21 . Besides, rat PSCs exhibit rapid loss of genomic imprints in culture, which affects their developmental potential, as judged by tetraploid complementation experiments designed to produce an entirely PSC-derived animal 22 , 23 . Here, we show that the use of rat blastocyst from Prdm14 KO rats serve as excellent hosts for the germline transmission of donor cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, rat PSCs are less robust than mouse PSCs, partly because of the difficulties of handling and clonal selection after genetic manipulation 20 , 21 . Besides, rat PSCs exhibit rapid loss of genomic imprints in culture, which affects their developmental potential, as judged by tetraploid complementation experiments designed to produce an entirely PSC-derived animal 22 , 23 . Here, we show that the use of rat blastocyst from Prdm14 KO rats serve as excellent hosts for the germline transmission of donor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, when reanalyzing the SC datasets from previous studies ( 53 55 ) we noticed that the expression of RTL1 could be a marker to evaluate developmental potential of SCs in mammals. We found that 4N “on” mouse iPSCs (competent for tetraploid complementation) showed higher RTL1 expression than 4N “off” mouse iPSCs (incompetent for tetraploid complementation) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interspecies chimerism has been most successful in rodents, and these studies typically achieve a high proportion of chimerism and generate xenogeneic organs (Kobayashi et al, 2010;Isotani et al, 2011). The pluripotency levels of rodent PSCs are the highest known, as they are genuine naïve cells, and they can produce live offspring by tetraploid complementation, which is the most stringent (Zhao et al, 2009;Li et al, 2017). Recent studies on xenogeneic chimerism in mice and rats showed that the pluripotency of rat ESCs affected kidney organ reconstruction in mice (Goto et al, 2019), demonstrating that the pluripotency of the donor cells influenced xenogeneic chimerism.…”
Section: Discussionmentioning
confidence: 99%